Narrative approach in training programme for teachers - Saharuddin, Norzihani; Abdullah, Nur Surayyah Madhubala; Hussien, Suhailah (Fakultas Ilmu Tarbiyah dan Keguruan, UIN Syarif Hidayatullah Jakarta, 2017)
This article's purpose is to describe the examples of Narrative Approach and its relevance in teacher training programme in Malaysia. The paper begins with the discussion of the current Moral Education (ME) in Malaysia together with their Moral Education teacher training programme. Then this article will describe on how Narrative Approach can take part as a method that can developed moral reasoning of preservice teacher in their training programme. A variety of teaching technique such as drama, role-play, storytelling, etc. will be considered as strategies for infusing Narrative Approach as an educational approach in teachers’ training programme in Malaysia, particularly in Moral Education field.